2004
DOI: 10.1002/ajmg.a.30136
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric deletions of chromosome 9q: A novel microdeletion syndrome

Abstract: Fluorescent in situ hybridization (FISH) screening of subtelomeric rearrangements has resulted in the identification of previously unrecognized chromosomal causes of mental retardation with and without dysmorphic features. This article reports the phenotypic and molecular breakpoint characterization in a cohort of 12 patients with subtelomeric deletions of chromosome 9q34. The phenotypic findings are consistent amongst these individuals and consist of mental retardation, distinct facial features and congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 35 publications
6
62
0
3
Order By: Relevance
“…Hypotonia, affecting most KS patients, is also present in the current cases, and in patient 1, this effect occurs concomitantly with a tented upper lip (present in 70-75% of cases) and tongue protrusion (40-60%), as is often observed in hypotonic subjects. An increased frequency of dental anomalies, specifically neonatal teeth, retention of primary dentition, small teeth, spaced teeth, and broad alveolar margins, has been reported in this condition, with an overall prevalence of approximately 10-15% [Stewart et al, 2004;Neas et al, 2005;Willemsen et al, 2011;Kleefstra et al, 2015]. Consistently with literature data, the teeth of patient 2 are small and spaced apart.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Hypotonia, affecting most KS patients, is also present in the current cases, and in patient 1, this effect occurs concomitantly with a tented upper lip (present in 70-75% of cases) and tongue protrusion (40-60%), as is often observed in hypotonic subjects. An increased frequency of dental anomalies, specifically neonatal teeth, retention of primary dentition, small teeth, spaced teeth, and broad alveolar margins, has been reported in this condition, with an overall prevalence of approximately 10-15% [Stewart et al, 2004;Neas et al, 2005;Willemsen et al, 2011;Kleefstra et al, 2015]. Consistently with literature data, the teeth of patient 2 are small and spaced apart.…”
Section: Discussionsupporting
confidence: 77%
“…Their auxological parameters were within a normal range, except for OFC: patient 2 is relatively microcephalic, whereas patient 1 is macrocephalic. Microcephaly is considered one of the hallmarks of this syndrome, as a relative or absolute, congenital or acquired reduction of the OFC is observed in more than half of the KS patients [Stewart et al, 2004]; this report is the first to describe an OFC >97th centile in KS.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of previous deletions were reported before genomewide array platforms became common use in routine diagnostic settings, and were either detected by routine FISH or MLPA [Dawson et al, 2002;Cormier-Daire et al, 2003;Font-Montgomery et al, 2004;Iwakoshi et al, 2004;Neas et al, 2005]. Some studies reported fine-mapping of deletions with additional specific 9q probes Stewart et al, 2004]. Only 2 previously reported deletions were cytogenetically visible, indicating that large cytogenetically visible deletions are a relatively rare cause of KS [Schimmenti et al, 1994;Ayyash et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome is either caused by a submicroscopic deletion in the chromosomal region 9q34.3 or an intragenic mutation of the euchromatin histone methyltransferase 1 (EHMT1) gene causing haploinsufficiency of EHMT1 . So far, 85 patients, including 75 patients with a 9q34.3 deletion and 10 patients with an EHMT1 mutation, have been reported [Schimmenti et al, 1994;Ayyash et al, 1997;Dawson et al, 2002;Cormier-Daire et al, 2003;Font-Montgomery et al, 2004;Harada et al, 2004;Iwakoshi et al, 2004;Stewart et al, 2004;Neas et al, 2005;Yatsenko et al, 2005Yatsenko et al, , 2009Kleefstra et al, 2006aKleefstra et al, , b, 2009Stewart and Kleefstra, 2007;Verhoeven et al, 2010;Willemsen et al, 2011]. EHMT1 encodes a histone H3 Lys 9 methyltransferase and is thereby involved in chromatin remodeling [Ogawa et al, 2002].…”
mentioning
confidence: 99%
“…This syndrome is characterized by severe mental retardation, hypotonia, microcephaly and a typical face with midface depression, hypertelorism, everted lower lip, cupid bow configuration of the upper lip, and a prominent chin. The minimum critical region involved is ϳ 1.2 Mb in size and encompasses at least 14 genes (Stewart et al, 2004). In a mentally retarded patient with a typical 9qter deletion phenotype, a balanced translocation t(X;9) (p11.23;q34.3) was detected (Kleefstra et al, 2005).…”
Section: Cytogenetic Microdeletion Syndromes and The Impact Of Singlementioning
confidence: 99%